Extended Postoperative Prophylactic Antibiotics for Primary and Aseptic Revision Total Joint Arthroplasty: A Systematic Review. Issue 11 (1st June 2022) - Yakkanti, Ramakanth R.; Vanden Berge, Dennis; Summers, Spencer H.; Mansour, Kailey L.; Lavin, Alessia C.; Hernandez, Victor H.
Abstract : Introduction: Limited literature is available about the effects of extended (>24 hours) antibiotic use after primary and aseptic revision total joint arthroplasty (TJA) on rates of periprosthetic joint infection (PJI). The purpose of this study was to systematically review the outcomes of extended prophylactic antibiotic use. Methods: A systematic search on PubMed and EMBASE databases was done in August 2021 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles that met inclusion criteria were screened by two separate authors. Basic patient demographics, route of delivery, type, dose, frequency of the antibiotic, rates of PJI, and length of stay were extracted. Results: A total of 11 articles published from 1979 to 2021 were included in the final analysis. Two studies evaluated aseptic revisions, seven evaluated primary TJA, and two studies evaluated both. Five studies were randomized controlled trials, one multicenter nonrandomized trial, and five retrospective cohort studies. All 11 studies used a cephalosporin or a penicillin antibiotic in both the control and cohort groups. Five studies used intravenous (IV) antibiotics, one study used oral (PO) antibiotics, and the other five studies used both IV and PO antibiotics. Length of stay was reported in three studies, all using IV antibiotics. All 11 studies evaluated rates of PJI, while four studies evaluated included rates of superficial surgical site infections. Four studies showed a statistically significant decrease in PJI when compared with a control group, while seven studies showed no statistically significant difference. Conclusion: There is conflicting evidence regarding the benefit of extended (>24 hours) antibiotics, IV or PO, after TJA. As of now, current guidelines do not support the use of extended antibiotics; future prospective clinical trials are needed to help support these claims.